Managing digital transformation of organisational culture and its shaping factors in the context of digitalisation - I. V. Groshev; He Menin (Вестник университета)
The article considers the processes of organisational culture management in the conditions of digitalisation. It is indicated that its digital transformation in the modern global market is one of the conditions for the survival of companies, the main components of which are presented by the authors in the form of a model. The advantages of the digital organisational culture and difficulties of the process of its digital transformation are considered separately. The key elements of the digital organisational culture and the arisen processes of change and transformation are analysed in detail. The latter affect the strategy, structure, and management processes of the organisation, and are aimed at optimising the management system, ensuring a balance between personnel and technology. At the same time, the authors emphasise that it is extremely difficult to formulate a general systemic picture of the digital organisational culture. As a conclusion, it is noted that at the present stage of the development of the Russian economy, the digital organisational culture provides certain advantages by influencing the formation of the organisational structure, creates a positive and constructive working environment, forces companies to set new goals and change their activities. As a result, the digital transformation of the organisational culture of companies can help reduce operating costs, promote the creation of new products and services or improvement of the existing ones, and improve the quality of interaction with customers and employees.